2022
DOI: 10.1016/j.tranon.2021.101320
|View full text |Cite
|
Sign up to set email alerts
|

Invasive phenotype in triple negative breast cancer is inhibited by blocking SIN3A–PF1 interaction through KLF9 mediated repression of ITGA6 and ITGB1

Abstract: Highlights We show that the PAH2 domain of SIN3A is a target when it is inhibited from binding to PF1 results in inhibition of invasive phenotype in TNBC. Epigenetic repression of integrins expression and downstream pathways results from enhanced binding of KLF9 /SIN3A repressor complex to their promoters. Genome wide transcriptomic analysis showed downregulation of multiple invasion related genes. Tumor growth and lung metastasis were markedly decreased i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…Our efforts also identified integrin α-6 as another molecule that accumulated on the cell surface when normal LOXL4 was abundantly expressed ( Supplementary Figure S2C ). The heterodimer complex combination of integrin α-6 and integrin β-1has been reported to promote cancer metastatic outgrowth in MDA-MB-231 cells ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our efforts also identified integrin α-6 as another molecule that accumulated on the cell surface when normal LOXL4 was abundantly expressed ( Supplementary Figure S2C ). The heterodimer complex combination of integrin α-6 and integrin β-1has been reported to promote cancer metastatic outgrowth in MDA-MB-231 cells ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblasts with high GSL metabolism pathway activity can communicate with smooth muscle cells through PDGFD-PDGFRB interaction, which functions in fibrosis and neovascular formation ( 31 ). Besides, fibroblasts with high GSL metabolism pathway activity can also communicate with keratinocytes through ITGA6-ITGB1 interaction, which play a role to promote cancer cell invasion and metastasis in a variety of cancers, such as cholangiocarcinoma and triple-negative breast cancer ( 32 , 33 ). In addition, the fibroblasts with high GSL metabolism pathway activity can communicate with endothelial cells through the SEMA3B signaling pathway, while SEMA3B is known to be an inhibitor of angiogenesis and cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…17 For example, it is reported that specific targeting of SIN3A results in suppression of invasion and metastasis related genes in breast cancer. 18 SIN3A is discovered to be overexpressed in CRC cells and tissues, and SIN3A silencing overtly hampers CRC cell proliferation, migration, and invasion. 19 Since m 6 A modification plays a role in tumors by modulating the biological processes of mRNA, such as stability, translation, and splicing, 5 we accordingly speculate that RBM15-mediated m 6 A modification can affect CRC progression and metastasis via the KLF1/SIN3A axis in an IGF2BP3-dependent manner.…”
Section: Introductionmentioning
confidence: 99%